THE INFLUENCE OF PSYCHOLOGICAL CONTRACTS ON JOB SATISFACTION AND ITS CONSEQUENCES ON JOB HOPING: A CASE STUDY IN KUPANG CITY USING THE THEORY OF PLANNED BEHAVIOR APPROACH - Burin, Stefanie Noviega Bribin; Firmansyah, Mariano (Universitas Gunadarma, 2024)
Job hooper are currently growing, especially among employees who are just starting their careers at a young age or in the millennial generation compared to previous generations. Employees who are still starting their careers are young employees who have just started working and still want to find a workplace that suits their desires and expectations. The aim of this research is to explain the influence of the psychological contract on job hopping with job satisfaction as a mediator for employees in Kupang City using the theory of planned behavior (TPB) approach. This research used quantitative methods, by distributing 171 questionnaires and 129 employees which fulfils certain criteria. The sampling method uses purposive sampling, with the criteria being employees who have worked for less than 2 years in a private company or have honorary employment status in an agency. Distributing the questionnaire using Google Form and using SEM-PLS as an analysis tool. The results of this research show that the psychological contract has a positive and significant effect on job satisfaction, while whether directly or indirectly through job satisfaction, the psychological contract has a negative and insignificant effect on job hoping.